Flake aluminum reinforced polyamideimide-polytetrafluoroethylene bonded solid lubricating composite coating for wear resistance and corrosion protection. (5th June 2021) - Li, Guihua; Ma, Yanjun; Wan, Hongqi; Chen, Lei; An, Yulong; Ye, Yinping; Zhou, Huidi; Chen, Jianmin
Graphical abstract: We develop a flake aluminum reinforced polyamideimide-polytetrafluoroethylene bonded solid lubricating composite coating with excellent tribological properties and corrosion resistance. Highlights: A flake aluminum reinforced PAI/PTFE bonded solid lubricating coating was prepared. The mechanical properties and wear resistance of the coating was greatly improved. The flake aluminum remarkably improved the corrosion resistance of the coating. Tribological and corrosion protection mechanisms of coatings were investigated. Abstract: A flake aluminum reinforced polyamideimide-polytetrafluoroethylene bonded solid lubricating composite coating (denoted as PAI/PTFE/Al) with excellent tribological properties and corrosion resistance was prepared via spraying process. The tribological properties of the coatings were measured through a CSM friction and wear tester. The corrosion resistance of the coatings was studied by the micro-electrochemical technique and the macroscopic salt spray test. The focus was on the influence of flake aluminum on the tribological properties and corrosion resistance of the coatings. The results showed that the mechanical properties, tribological properties and corrosion resistance of the PAI/PTFE/Al bonded solid lubricating composite coating containing 30 wt% flake aluminum reached the optimum compared with the PAI/PTFE composite coating. The improvement of the tribological properties of the composite coating was attributed to the excellent mechanical properties of flake aluminum and the good lubrication of PTFE. The enhancement of the corrosion resistance of the composite coating was the result of the combined effect of PTFE with hydrophobic properties and flake aluminum with excellent shielding effect and cathodic protection.